SPATIAL AUTOREGRESSIVE MODEL (SAR) AND SPATIAL ERROR MODEL (SEM) MODELING ON LIFE EXPECTANCY DATA IN SOUTH SULAWESI PROVINCE 2022 - Hafid, Hardianti; Ayu Pebriyanti; Sudarmin (Parameter: Journal of Statistics, 2025)
Spatial regression is a development of classical linear regression which takes into account the spatial or spatial effects of the data being analyzed. The Spatial Autoregressive Model (SAR) and Spatial Error Model (SEM) methods include spatial regression models show that spatial effects on response variables and predictor variables. This research aims to model the factors that influence life expectancy in South Sulawesi Province in 2022. The analysis method used in this research is the SAR and SEM methods. The results show that based on the Lagrange Multiplier test values, there are lag and error dependencies. Based on the research results, it was found that the SAR and SEM models each had Akaike’s Information Criterion (AIC) values of 94.0069 and 90.6410, so the best model for analyzing the influence life expectancy value was the SEM model because the smallest had Akaike’s Information Criterion (AIC) value was obtained. The factors that have a significant influence on life expectancy are average years of schooling and gross regional domestic product which have a positive effect. Then, the percentage of poor population and per capita expenditure have a negative effect.